A Re-education on How to Work: Vocational Programs in Kingston-Area Prisons, 1950–1965 - McNeill, Katie-Marie (Labour / Le Travail, 2022)
The Prison for Women, Kingston Penitentiary, and Collins Bay Penitentiary each offered an increasing variety of vocational training opportunities to incarcerated people in the mid-20th century. This article examines vocational training in these Kingston-area prisons from 1950 to the mid-1960s and argues that access to these programs was based largely on gender and age. Foucault’s idea of governmentality supports analysis of how the Penitentiary Service of Canada, reformers, and prisoners understood the process of learning how to work. Women incarcerated at the Prison for Women were trained in fields that mirrored domestic labour, and limited numbers of younger women were given access to trial vocational training in women-dominated fields such as hairdressing. Young men in their teens and twenties incarcerated at Collins Bay Penitentiary were given access to skilled trades, while older men at Kingston Penitentiary could try to qualify for transfer to Collins Bay Penitentiary by taking basic educational course upgrades. These vocational programs were supported by the John Howard Society of Ontario and the Elizabeth Fry Society of Kingston, local prisoner aid societies that helped formerly incarcerated people find jobs and coordinated with prison administration to bolster rehabilitation programs.